The last unicorn : the lost journey - Beagle, Peter S. (Tachyon Publications, 2018)
"Peter S. Beagle first imagined his beloved heroine when he was twenty-three, half a decade before she sprang into the world. Now the Last Unicorn's fantastical origins are recaptured in this beautifully illustrated, commemorative hardcover edition, which includes Beagle's revisited, wry musings upon his early writing career. In this appealingly familiar yet wonderfully strange adventure, a brave unicorn leaves her solitary life behind, determined to discover if she is the last of her kind. She is forewarned by a forlorn dragon and befuddled by a chatty butterfly; her traveling companion is an exiled demon with a split personality and a penchant for philosophy. Somewhere between mythology, modernity, and magic, the last unicorn is finding her world irrevocably transformed." --